Head impact mechanisms during practice for soccer of junior athletes - O'Sullivan, D. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Since the high number of deaths (suicides) and debilitating head injuries in American Football there has been a lot of attention both by the media and by researchers for head injuries in sport. However, soccer is reported to be responsible for the largest number of head impacts and highest concussion rates among females (Gessel et al., 2007). Only recently the technology to measure head impact mechanisms during practice and competition is available and so there is a dearth of data regarding the magnitudes and frequency of head impacts in soccer for all genders and levels. Therefore the purpose of this study was to measure the head impact characteristics of junior boys during soccer practice. Methods: Using the xPatch (Biosystems Inc.) head impact data (peak linear acceleration (PLA), peak rotational acceleration (PRA), peak rotational velocity (PRV) and Head injury Criterion (HIC) 15ms) were collected over ten training sessions. Ten junior boys aged between 8 and 12 years of age participated after their parents/ guardians signed the University Hospital approved IRB consent form. Data from the sensor was then backed up on the Biosystems cloud and their proprietary software Impact Management System software was used to output the impact severity related variables. Non-parametric Krushall-Wallis tests were used to investigate the differences in the sessions and among the participants. Results: During the ten sessions, there were a total of 501 impacts recorded, averaging out at 90 impacts per 100 minutes. The averages and standard deviations for PLA, PRA, PRV and HIC were 17.8±10.3g, 3168 ± 2442deg/s2, 16.1 ± 10.6deg/s, 11.4 ± 34.2. The most impacts were located at the back of the head (45.5%), followed by the side (33.7%)), front (19.9%) and top (0.9%). According to the PLA guidelines by King (2014) 96.2% were classified as low severity (10-39g), 3.3% medium severity (40-69g), and 0.4% as high severity (<70g). Discussion: With the exception of a few impacts (2 impacts) the magnitudes recorded in this study were not classified as a high severity. However, because of the high frequency of head impacts in soccer, it is important for those participating and their medical support staff to be aware of the risks associated with repetitive impacts. Future research is needed to maintain a longitudinal design to assess the effects of repetitive low impacts.